Moroccan Monofloral Bee Pollen: Botanical Origin, Physicochemical Characterization, and Antioxidant Activities - El Ghouizi Asmae; El Menyiy Nawal; Meryem Bakour; Badiaa Lyoussi (Journal of Food Quality)
In this study, eight monofloral bee pollen samples were collected from different apiaries in Morocco. Botanical origins of the bee pollen samples were determined by scanning electron microscopy (SEM), and the physicochemical parameters (pH, moisture, ash, and the mineral contents) were determined. Total phenolic, flavones/flavonols contents were evaluated, and the antioxidant potential was assessed using total antioxidant capacity, DPPH, ABTS, and reducing power assays. Data showed that pH, moisture, and ash content values ranged between 4.19 ± 0.17 and 4.82 ± 0.36, 10.7 ± 0.04% and 26.8 ± 0.01%, and 1.81 ± 0.10% and 4.22 ± 0.08%, respectively. Potassium and magnesium were the most abundant minerals in bee pollen samples; heavy metals were not detected except for two samples (P5 and P6) where a very small amount of lead was found. The protein content in these samples varied between 19.86 ± 0.36 mg/100 g and 30.32 ± 0.12 mg/100 g of bee pollen. The phenolic content, flavones/flavonols content, and total antioxidant capacity were 21.87 ± 1.80 mgEAA/g, 2.37 ± 0.16 mgEAA/g, and 6.23 ± 0.21 mgEAA/g, respectively. High scavenging activity of DPPH and ABTS radicals was found in P2 with the lower IC50 of 0.245 ± 0.009 mg/ml and 0.19 ± 0.005 mg/ml, respectively. The lower EC50 was 0.133 ± 0.036 mg/ml found in P1 for the reducing power test. The current study is considered to be the first step to the standardization of Moroccan bee pollen.